Business model reinvention: Impacts of Covid-19 in the hospitality business - Adam, Olexandr (2020)
At the moment, the hospitality business is facing serious challenges due to the COVID-19 pandemic, which is forcing hotels to quickly adapt to a new operational reality. Such adaptation requires the redefinition of the current business models since they are not adequate for the current global scenario. The main goal of this dissertation is to analyse the main impacts of COVID-19 in the hospitality business and to ultimately propose a general reinvented business model, aiming to contribute to the hospitality industry’s reinvention in the global scenario. To fulfil these objectives, a literature review was developed, and an in-depth interview was conducted with 14 professionals, who work at different hotels. The interview aimed to assess nine building blocks, all related to the business model implemented by hotels: key partners, activities, resources, value proposition, customer relationship, channels, customer segments, cost structure, and revenue streams. Overall, the obtained results demonstrated that the reinvention of the hotels’ business model must include a significant investment in technology and digital communication, since these two dimensions are vital for the industry’s growth and evolution, since they provide customers with a sense of trust and confidence towards hotels.